The role of evidence in proving the crime: the perspective of Sunnis - Rezai, Ali Ahmad; Abdullahi Nejad, Abdul Karim; Sultani, Abbas Ali (Opción, 2019)
The aim of study is to investigate the role of circumstantial evidence in proving the crime that should be punished in terms of the perspective of the Sunni jurisprudence by looking at the rights of Afghanistan through qualitative and data-based methods. As a result, the criterion of proof from the point of view of Afghan criminal law is the presented evidence to the court. As a conclusion, the Afghan legislator explains the credibility and proving the role of circumstantial evidence in a very clear manner, and the judiciary judges and trials use this tool and a great opportunity.